2011
DOI: 10.1016/j.joca.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative interventions (non-surgical and non-pharmacological) for patients with hip or knee osteoarthritis awaiting joint replacement surgery – a systematic review and meta-analysis

Abstract: Low to moderate evidence from mostly small RCTs demonstrated that pre-operative interventions, particularly exercise, reduce pain for patients with hip and knee osteoarthritis prior to joint replacement, and exercise with education programs may improve activity after hip replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 58 publications
8
139
0
4
Order By: Relevance
“…As a result of 8-week HEP, pain intensity in knee joint decreased, whereas self-reported function of knee joint did not improve significantly. Similar results of the WOMAC index score have also been found by previous studies with patients with knee OA [20]. Preoperative performance of HEP is recommended for improvement of surrounding knee joint muscle function.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As a result of 8-week HEP, pain intensity in knee joint decreased, whereas self-reported function of knee joint did not improve significantly. Similar results of the WOMAC index score have also been found by previous studies with patients with knee OA [20]. Preoperative performance of HEP is recommended for improvement of surrounding knee joint muscle function.…”
Section: Discussionsupporting
confidence: 87%
“…Patients often have to wait several months for the surgery and during that time they endure severe pain that restricts their activities of daily living (ADL) and participation in their normal social roles. Pre-operative interventions such as exercises are performed in the expectation of improving pre-operative outcomes as well as recovery after surgery [20]. There is much evidence suggesting that exercises are effective in OA patients for decreasing pain and improving function [5,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEDro score has demonstrated moderate interrater reliability (intraclass correlation coeffi cient = 0.68 [95% CI, 0.57-0.76]) for clinical trials 15) . A trial with a score of 6 or more was considered to be high quality, which is consistent with previous reviews 16) .…”
Section: Risk Of Bias In Individual Studiessupporting
confidence: 66%
“…Furthermore, studies have shown that, for other musculoskeletal injuries, good preoperative function is essential for good postoperative results. 21,38,41,65,68 Hence, teaching patients appropriate exercises to perform and using a structured exercise program to optimize preoperative knee function could also be of potential benefit for patients with full-thickness articular cartilage lesions who require a surgical repair.…”
Section: The Oslo Cartilage Active Rehabilitation and Education Programmentioning
confidence: 99%